2018
DOI: 10.1093/aje/kwy183
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality Indices and Risk of Type 2 Diabetes Mellitus

Abstract: We aimed to test whether predefined dietary patterns that are inversely related to risk of type 2 diabetes (T2D) in Western populations were similarly associated with lower T2D risk in an Asian population. We included 45,411 middle-aged and older participants (ages 45-74 years) in the Singapore Chinese Health Study who were free of diabetes, cancer, and cardiovascular disease at baseline (1993-1998). Participants were followed up for T2D diagnosis through 2010. Dietary information was collected using a validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 37 publications
7
61
0
Order By: Relevance
“…However, our results indicate that the presence of dyslipidemia was associated with a higher aMED score. Scientific studies published about this issue found that the MedDiet reduces the risk of T2D improving postprandial lipemia, lipid profile, and cardiovascular risk factors [3,4,[38][39][40][41][42][43]. Our results could be due to the fact that participants with dyslipidemia may have received specific dietary counselling based on the MedDiet to improve their lipid profile.…”
Section: Discussionmentioning
confidence: 71%
“…However, our results indicate that the presence of dyslipidemia was associated with a higher aMED score. Scientific studies published about this issue found that the MedDiet reduces the risk of T2D improving postprandial lipemia, lipid profile, and cardiovascular risk factors [3,4,[38][39][40][41][42][43]. Our results could be due to the fact that participants with dyslipidemia may have received specific dietary counselling based on the MedDiet to improve their lipid profile.…”
Section: Discussionmentioning
confidence: 71%
“…The direction of the associations was mostly consistent across all ethnic groups [ 17 ]. The AHEI has been shown to be inversely associated with the risk of having T2DM in an Asian population aged 45–74 years (multivariable-adjusted hazard ratio 0.93 per 1-SD increase in score) [ 19 ]. A stratified analysis revealed a significant interaction effect of smoking on the association which was only present in non-smokers (p-interaction 0.03) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AHEI has been shown to be inversely associated with the risk of having T2DM in an Asian population aged 45–74 years (multivariable-adjusted hazard ratio 0.93 per 1-SD increase in score) [ 19 ]. A stratified analysis revealed a significant interaction effect of smoking on the association which was only present in non-smokers (p-interaction 0.03) [ 19 ]. This holds for the alternate MDS as well (multivariable-adjusted hazard ratio of 0.93 per 1-SD increase in score).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only one prospective study on plant-based diets has been conducted in an Asian population. In Singapore, a prospective cohort study found that higher adherence to PDI and hPDI was associated with a lower risk of type 2 diabetes [21].…”
Section: Plos Medicinementioning
confidence: 99%